IMPROVING EDUCATIONAL INNOVATION THROUGH ARTIFICIAL INTELLIGENCE AND DIGITAL CONTENT DEVELOPMENT WORKSHOPS - Baso Intang Sappaile; Norma Nasir; Ahmad Talib (Adiba Aisha Amira, 2026)
This community service activity aims to increase the capacity of educators to utilize AI technology and develop innovative digital content that can be applied in educational environments. Through a literature review-based approach, this research identifies various concepts, models, strategies and best practices related to the implementation of AI in education and the development of digital content that supports 21st century learning. The method used is a literature review by collecting, analyzing and synthesizing various scientific sources in the form of journal articles, conference proceedings, academic books and relevant research reports. The results of the study show that AI-based training and workshops are able to improve participants' abilities in designing digital learning media, produce more personalized material, speed up the content creation process, and encourage student-centered learning innovation. In addition, the integration of AI in digital content development contributes to improving the quality of learning, student engagement, and the readiness of educational institutions to face digital transformation.